Using cognitive work analysis to compare complex system domains*. (3rd September 2018) - D. St-Maurice, Justin; M. Burns, Catherine
ABSTRACT: There are several reasons to compare and transfer knowledge between complex socio-technical systems. For example, there have been attempts to transfer lessons and knowledge from aviation to health care. Conceptually, understanding system differences in complex environments can highlight the behaviours, processes, values and training that drive performance and ensure safety. Though various approaches exist, we show that an ecological framework, such as cognitive work analysis (CWA), provides an ideal opportunity for the rich comparison of complex systems. This approach is novel, as previous studies have rarely analysed cognitive work analysis models from multiple domains or drawn comparisons. Through a case study, we demonstrate the comparison of work domain analyses and control task analyses from two similar but different health care domains. Through a detailed description of our comparison in a health care setting, we demonstrate that unique and useful insights can be extracted through this process. Though this approach is prefatory, it merits further refinement and use and presents a new way to consume CWA models that currently exist in the literature.